Experimental Liquid Densities of Red Palm Oil at Pressures up to 150 MPa from (312 to 352) K and Dynamic Viscosities at 0.1 MPa from (293 to 353) K - Jia Lin Lee; Gun Hean Chong; Yuya Hiraga; Yoshiyuki Sato; Masaki Ota; Richard Lee Smith (Liquids)
Density and viscosity are fundamental properties necessary for processing of red palm oil (RPO). The main fatty acid constituents of RPO were determined to be palmitic acid (C16:0), oleic acid (C18:1), and linoleic acid (C18:2). Rheology measurements confirmed that RPO behaved as a Newtonian fluid. Viscosities and atmospheric densities of RPO were measured at 0.1 MPa and (293 K to 413) K and correlated with the Rodenbush model (0.05% deviation). Dynamic viscosities of RPO were correlated with the Vogel–Fulcher–Tammann model (0.06% deviation) and Doolittle free volume model (0.04% deviation). High-pressure densities of RPO were measured at (10 to 150) MPa and (312 to 352) K. The Tait equation could correlate the high-pressure densities of RPO to within 0.021% deviation and was used to estimate the thermal expansion as 5.1 × 10−4 K−1 (at 312 K, 150 MPa) to 4.8 × 10−4 K−1 (at 352 K, 150 MPa) and isothermal compressibility as 7.3 × 10−4 MPa−1 (at 352 K, 0.1 MPa) to 3.5 × 10−4 MPa−1 (at 352 K, 150 MPa). Parameters for the perturbed-chain statistical associating fluid theory equation of state were determined and gave an average of 0.143% deviation in density. The data and equations developed should be useful in high-pressure food processing as well as in applications considering vegetable oils as heat transfer fluids or as lubricants.